Addition of efficient microorganisms in the feeding of pigs (Sus scrofa domesticus) in the growth and fattening stage (Agroindustria, Sociedad y Ambiente, 2024)
Ecuador is a leading country in the agricultural sector, but it has deficiencies in the swine sector. This problem is worsening even more due to the lack of knowledge of the producers about the alternatives that can increase swine productivity. Therefore, the objective of this research was to evaluate the addition of efficient microorganisms in the feeding of pigs (Sus scrofa domesticus) in the growth and fattening stage. A Completely Randomized Experimental Design (C.A.D.) was used, evaluating 3 treatments plus 1 control treatment with 3 replicates. The different concentrations of efficient microorganism had a significant influence (p
Keywords: feeding; pigs; efficient microorganisms; productive parameters